RNA cancer vaccines: developing mRNA nanovaccine with self-adjuvant property for cancer immunotherapy - Hongxia Zhang; Xiaojun Xia (Taylor & Francis Group, 2021)
Messenger RNA (mRNA)-based cancer vaccine has become a popular approach for developing personalized and effective antitumor immunotherapy. To achieve robust antitumor efficacy, mRNA-encoding tumor antigens needs to be efficiently delivered and translated in dendritic cells for efficient antigen presentation; meanwhile, the vaccine would have adjuvant effect by stimulating innate immune response to boost the full activation of adaptive immunity. Recently, we reported a minimalist nanovaccine by formulating tumor antigen-encoding mRNA with a lipid-like material named C1, which could efficiently deliver mRNA into dendritic cells with simultaneous Toll-like receptor 4 (TLR4) stimulation, together induced T cell activation. Importantly, C1 mRNA nanovaccine exhibited significant antitumor efficacy on several tumor mouse models. Here, we discuss the nanovector-facilitated mRNA delivery and translation in dendritic cells, the self-adjuvant property of nanovectors, the challenges of personalized tumor antigen selection, and the potential strategies for developing efficacious mRNA cancer vaccines targeting the immunosuppressive tumor microenvironment.